Infectious Aortic Root Pseudoaneurysm after Bentall Procedure: To Treat or Not to Treat by Redo Operation? - Saitto, Guglielmo; Russo, Marco; Pugliese, Marta; Vacirca, Sara R.; Bertoldo, Fabio; Nardi, Paolo; Ruvolo, Giovanni (AORTA, 2019)
We present a case of a 75-year-old man who developed an early aortic bioprosthesis endocarditis due to Klebsiella pneumoniae complicated by aortic root pseudoaneurysm after Bentall procedure. A prompt surgical option was hypothesized, but we decided to wait and keep on clinical observation and antibiotic therapy. One year after discharge, we observed stable clinical conditions and echocardiographic findings. A question: to treat or not to treat by redo operation an infectious aortic root pseudoaneurysm?
Keywords: prosthetic valve endocarditis; aortic root pseudoaneurysm; redo operation